Parent Perspectives on Their Mobile Technology Use: The Excitement and Exhaustion of Parenting While Connected. Issue 9 (November 2016) - Radesky, Jenny S.; Kistin, Caroline; Eisenberg, Staci; Gross, Jamie; Block, Gabrielle; Zuckerman, Barry; Silverstein, Michael
ABSTRACT: Objective: Parent use of mobile devices (e.g., smartphones, tablets) while around their young children may be associated with fewer or more negative parent-child interactions, but parent perspectives regarding this issue have not been explored. We aimed to understand parent views regarding their mobile device use to identify actionable targets of potential intervention. Method: We conducted 35 in-depth semi-structured group and individual interviews with English-speaking caregivers of children 0 to 8 years old, purposively sampled from diverse ethnic backgrounds, educational levels, and employment statuses. Following thematic saturation, results were validated through expert triangulation and member checking. Results: Participants included 22 mothers, 9 fathers, and 4 grandmothers; 31% were single parents, 43% nonwhite race/ethnicity, and 40% completed high school or less. Participants consistently expressed a high degree of internal tension regarding their own mobile technology use, which centered around 3 themes relevant to intervention planning: (1) Cognitive tensions (multitasking between work and children, leading to information/role overload), (2) emotional tensions (stress-inducing and reducing effects), and (3) tensions around the parent-child dyad (disrupting family routines vs serving as a tool to keep the peace). Conclusion: Caregivers of young children describe many internal conflicts regarding their use of mobile technology, which may be windows for intervention. Helping caregivers understand such emotional and cognitive responses may help them balance family time with technology-based demands.